(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
Based on the case study of the improv theater collective Baby Pedra e o Alicate, the investigation aims to analyze how the creative processes of improvising actors can be streamlined and overvalued through the discipline of the mask and, mainly, the animated forms. The text seeks to provide relevant considerations for improvisers and manipulative artists, concluding that, while improvisation “in the heat of the action” can be an effective perspective to dynamize the actor’s work in the theater of animated forms, the insertion of animants in the improvised scene also demonstrates to have a potential for effectiveness to elevate improvisation theater to a level of excellence.